Pengaruh Latihan Metode Drill Terhadap Kemampuan Passing Bawah Bola Voli Tim UNIMUDA Sorong - Deki Obinaru, Rais; Istiyono; Sugiono (Jurnal Muara Olahraga, 2024)
This research aims to determine the effect of drill method training on the under-passing ability of the UNIMUDA Sorong volleyball team. This research is a pre-experimental one club pretest and posttest design research where this research does not have a comparison group. The population in this study was the UNIMUDA Sorong men's volleyball team who took part in a volleyball match totaling 12 people, without any comparison group. Data analysis techniques are normality test, homogeneity test and t test for hypothesis testing, and samples are correlated at a significance level of 5%. The test results show that there is an influence of Drill method training on increasing bottom passing ability. Hypothesis testing shows the calculated t value (3.33) > t table (2.080), and p value (0.003) < 0.05, so this shows that Ho is rejected and Ha is accepted, which means there is a significant difference in increasing bottom passing ability after being given treatment. with the drill training method. Based on the research results, it shows that the average pretest score percentage shows an average of 5.4167% and is greater than the average protest score of 9.8333%. From these results it can be concluded that there is a significant influence of training methods on improving the passing ability of the Unimuda Sorong volleyball team. The percentage increase in lower passing ability was 18.61% from the pretest average difference multiplied by 100%.